Developing Materials For Special Academic Purposes For Islamic Education Using Google Apps For Education/ تطوير المادة الدراسية الأكاديمية لقسم التربية الإسلامية عبر تطبيقات جوجل التربوية - Darmawaty, Ridha; Ainin, Muhamad; Mujab, Muhammad; Saidi, Ahmad (Universitas Islam Negeri Maulana Malik Ibrahim Malang, 2021)
Teaching reading skills based on interactive construction theory requires more complex teaching materials because the process involves the interaction between students and teaching materials in the form of direct information and latent information. In addition, the facts on the field show that the characteristics of adult learners are more likely to choose to study in comfortable places and more appropriate times. Therefore, teaching language using Google Apps is one of the best solutions to answer this problem. This research aims to develop a model of reading materials for special academic purposes for Islamic Education using the Google Apps for Education. The method used in this research is Research and Development method. The result of the research is as follows; (1) Using reading materials according to the learner’s need made them easier to understand how to determine their function in various model of sentences and the material is more in line with the needs of the learners. (2) This research reinforces Krashen’s input hypothesis idea, while the characteristics of the resulting material in this research reinforce Stravens’ theory of elements language programs for a special purpose. At last, using Google Application for Education in developing materials can encourage students to study more since it is more interactive and in line with students’ need